2011
DOI: 10.1590/s0103-84782011000100026
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma bronquíolo-alveolar difuso em um cão: aspectos clínico-patológicos e imuno-histoquímicos

Abstract: A 12-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…Histopathological evaluation was compatible with lepidic predominant adenocarcinoma, in accordance with other studies that demonstrated this neoplasia is characterized by the proliferation of neoplastic cells along the pulmonary alveoli and pre-existing bronchioloalveolar junctions [3,6,11]. This classification of lung tumors in humans and animals is based on the site of origin and/or histological patterns [11].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Histopathological evaluation was compatible with lepidic predominant adenocarcinoma, in accordance with other studies that demonstrated this neoplasia is characterized by the proliferation of neoplastic cells along the pulmonary alveoli and pre-existing bronchioloalveolar junctions [3,6,11]. This classification of lung tumors in humans and animals is based on the site of origin and/or histological patterns [11].…”
Section: Discussionsupporting
confidence: 87%
“…The most frequent clinical sign in dogs with this disease is chronic cough, non-responsive to antibiotics, reinforcing the silent behavior of the disease [6,7]. This fact impairs an early intervention since it can be confused with other respiratory diseases, thereby delaying appropriate care for the patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations